2009
DOI: 10.1161/circulationaha.108.843615
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Medical Therapy and Timely Operation in Initially Diagnosed Type A Aortic Intramural Hematoma

Abstract: Background-The management of aortic intramural hematoma (IMH) involving the ascending aorta (type A) has not been well-established. The purpose of this study was to clarify the long-term clinical outcomes of patients with type A IMH who were treated with medical therapy and timely operation. Methods and Results-Clinical data including operative mortality, IMH-related events, and long-term survival were retrospectively reviewed in 66 patients with type A IMH, who were admitted to our institution from 1986 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 25 publications
5
121
0
6
Order By: Relevance
“…The proportion of patients who eventually required urgent surgery was 32% in Song's study and similar to other reported series (27,31,33). Song and others identified aortic diameter (>50-55 mm) and thickness of the IMH (>10-16 mm) as risk factors for death, rupture and conversion to AD in patients who are medically treated (27,33).…”
Section: Intramural Hematoma (Imh)supporting
confidence: 84%
See 1 more Smart Citation
“…The proportion of patients who eventually required urgent surgery was 32% in Song's study and similar to other reported series (27,31,33). Song and others identified aortic diameter (>50-55 mm) and thickness of the IMH (>10-16 mm) as risk factors for death, rupture and conversion to AD in patients who are medically treated (27,33).…”
Section: Intramural Hematoma (Imh)supporting
confidence: 84%
“…The proportion of AAS that is diagnosed as IMH is larger in Asians vs. Americans and Europeans (31). Some Asians (Japanese and Koreans) can be managed initially without surgery and surgery is reserved for those who develop complications of the IMH with very good outcomes (27,33). However, in North Americans, Europeans and Chinese, the mortality of medical management is prohibitively high and emergent or urgent surgical intervention is recommended (24,25,30,32).…”
Section: Intramural Hematoma (Imh)mentioning
confidence: 99%
“…Despite the present gaps in our knowledge of their natural history, popular management approach for ATAIMH, especially in the Western experience (IRAD, Stanford, and other North American authors), continues to be similar to that of ATAAD involving urgent aortic repair (3,(5)(6)(7). On the other hand, most studies from the Far East recommend initial medical management, with surgery reserved for specific circumstances complicating the course of otherwise stable ATAIMH patients and have reported acceptable early and late outcomes (8)(9)(10). Table 1 highlights some of the major differences in the literature reporting experience in management of ATAIMH from the Western vs. Eastern centers.…”
Section: Introductionmentioning
confidence: 99%
“…19 ). In high risk patients without aortic dilatation (< 50 mm) and wall hematoma < 11 mm only medical therapy (hypertension and pain control) can be considered as initial treatment with follow-up CT examination 19,29 .…”
Section: Treatmentmentioning
confidence: 99%